2015
DOI: 10.17245/jdapm.2015.15.3.121
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamic changes associated with a novel concentration of lidocaine HCl for impacted lower third molar surgery

Abstract: BackgroundThe authors studied the hemodynamic effect influent by using the novel high concentration of lidocaine HCl for surgical removal impacted lower third molar. The objective of this study was to evaluate the hemodynamic change when using different concentrations of lidocaine in impacted lower third molar surgery.MethodsSplit mouth single blind study comprising 31 healthy patients with a mean age of 23 years (range 19-33 years). Subjects had symmetrically impacted lower third molars as observed on panoram… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
11
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 19 publications
4
11
1
Order By: Relevance
“…A previously published study used a 3-4 week interval between the first and second surgeries for patients with bilateral lower third molar surgery [ 3 4 12 ]. Therefore, we chose a 3-week interval between the surgeries in this study so that postoperative sequelae of the local anesthetic injection, such as pain and numbness, were reduced.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A previously published study used a 3-4 week interval between the first and second surgeries for patients with bilateral lower third molar surgery [ 3 4 12 ]. Therefore, we chose a 3-week interval between the surgeries in this study so that postoperative sequelae of the local anesthetic injection, such as pain and numbness, were reduced.…”
Section: Discussionmentioning
confidence: 99%
“…In many previous studies, researchers have tried to manipulate the physical and chemical properties of local anesthetics to improve their effectiveness when used for the inferior alveolar nerve (IAN) block. Researchers have compared different types and volumes [ 2 3 4 ] of local anesthetics and have modified the concentration of the buffering agent in the local anesthetic cartridge. Previous studies have commonly reported on the onset, duration of action, and success rate of pulpal anesthesia observed with the different methods [ 5 6 7 8 9 10 11 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Measurement of the patient's anxiety in this study was performed using alterations of hemodynamic parameters, such as blood pressure and heart rate [ 20 21 22 23 24 ]; however, the results showed no statistically significant difference in both the groups. Hence, decreased blood pressure and heart rate might not be accurate parameters for determining the anxiety of patients in a clinical setting.…”
Section: Discussionmentioning
confidence: 99%
“…Lidocaine and other local anesthetics, drugs commonly used in dentistry, may cause various adverse effects, although these are low in frequency [ 5 ]. Such adverse effects include immune response-mediated allergic reactions and others that are unrelated to the immune response [ 1 ].…”
Section: Discussionmentioning
confidence: 99%